(untitled) (World Economics and Finance Bulletin, 2025)
The Malaysian experience is one of the development experiences worthy of attention and study, and developing countries benefit from it in rising from stagnation and backwardness. The Malaysian experience came to focus on building the human being, fighting poverty, encouraging creativity, supporting self-reliance, and strengthening export policies. It is one of the first industrial countries in the Islamic world. In 1957, the trend towards industrialization policy began as a primary goal for development. The development strategy in the early sixties turned towards a strategy of compensating for imports in the field of consumer industries. By the mid-eighties, the Malaysian economy became based on manufacturing after it had been dependent on primary commodities, as its exports depend on industry for about (80-85%). Malaysia was able to establish and develop the infrastructure, and diversify its sources of national income, which contributed to achieving a solid economic structure, and achieved great successes in treating the problems of illiteracy, unemployment, and others